Transnational Corporations and Marketing Ethics - Chahal Aarti, Mahapatra, S.N. (International Journal of Scientific Research and Management (IJSRM), 2017)
In globalized world market transnational corporations are dominating world market. Transnational corporations are one of the most important actors in the global economy occupying a more powerful position than ever before. To increase profits they have increasingly turn to the developing world. Today they are some 65,000 of them with about 850,000 foreign affiliates across the globe. In the process of globalization the marketing ethics have not yet been globalized. Many transnational corporation in their relentless search for markets profits virtually severed their relationships with the societies that have nurtured them and acting as if they have no obligation to any one other than their own corporate interest. These unethical practices by TNCs may lead to far greater losses in the long run. The cost of ethical failure can be very high not just in financial penalties there can be a loss of trust and trust is important to all constituencies of business.